1993
DOI: 10.1073/pnas.90.8.3730
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13 induces interleukin 4-independent IgG4 and IgE synthesis and CD23 expression by human B cells.

Abstract: Recently the cDNA encoding interleukin 13 (IL-13), a T-cell-derived cytokine, was cloned and expressed. The present study demonstrates that IL-13 induces IgG4 and IgE synthesis by human B cells. IL-13-induced IgG4 and IgE synthesis by unfractionated peripheral blood mononuclear cells and highly purified B cells cultured in the presence of activated CD4+ T cells or their membranes. IL-13-induced IgG4 and IgE synthesis is IL-4-independent, since it was not affected by neutralizing anti-IL-4 monoclonal antibody. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
611
2
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 971 publications
(649 citation statements)
references
References 45 publications
19
611
2
9
Order By: Relevance
“…-1198 Immunity to infection IL-13, originally described as a T cell-derived antiinflammatory cytokine, has multiple biological activities. Like IL-4, IL-13 up-regulates CD23, CD71 and MHC class II expression on B cells and monocytes [32], elicits B cell proliferation and induces IgG4 and IgE production by human B cells [32], and promotes Th2 cell differentiation [33]. In addition, IL-13 plays a dominant role to IL-4 in mediating worm expulsion to Nippostrongylus brasiliensis [34], exerts protective functions both in the chronic stages of some Leishmaniasis major infections [35] and in Listeria monocytogenes infection in the context of a Th1 cytokine response [36], and acts as the key mediator in the pathogenesis of allergic asthma [37].…”
Section: Discussionmentioning
confidence: 99%
“…-1198 Immunity to infection IL-13, originally described as a T cell-derived antiinflammatory cytokine, has multiple biological activities. Like IL-4, IL-13 up-regulates CD23, CD71 and MHC class II expression on B cells and monocytes [32], elicits B cell proliferation and induces IgG4 and IgE production by human B cells [32], and promotes Th2 cell differentiation [33]. In addition, IL-13 plays a dominant role to IL-4 in mediating worm expulsion to Nippostrongylus brasiliensis [34], exerts protective functions both in the chronic stages of some Leishmaniasis major infections [35] and in Listeria monocytogenes infection in the context of a Th1 cytokine response [36], and acts as the key mediator in the pathogenesis of allergic asthma [37].…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 has been shown to share many of its biological activities with IL-4, although IL-13, in contrast to IL-4, does not act on human T cells [48]. Like IL-4, IL-13 induces CD23 expression on B cells, directs Ig isotype switching to IgG4 and IgE synthesis, and inhibits production of pro-inflammatory cytokines by monocytes [49,50]. However, the observation that IL-13 was less efficient in inducing B-cell differentiation than IL-4 is consistent with earlier results indicating that IL-13 is less potent than IL-4 in inducing IgE synthesis by normal human B cells [49], or immature fetal B cells [51].…”
Section: B-cell Differentiation In Patients With CVI 207mentioning
confidence: 99%
“…Like IL-4, IL-13 induces CD23 expression on B cells, directs Ig isotype switching to IgG4 and IgE synthesis, and inhibits production of pro-inflammatory cytokines by monocytes [49,50]. However, the observation that IL-13 was less efficient in inducing B-cell differentiation than IL-4 is consistent with earlier results indicating that IL-13 is less potent than IL-4 in inducing IgE synthesis by normal human B cells [49], or immature fetal B cells [51]. However, like IL-4, IL-13 might be useful in the treatment of some patients with defective humoral immunity, such as in SCID patients, who have mutations in their gene encoding the common g-chain, a component of receptors for IL-2, IL-4, IL-7, IL-9 and IL-15 [52][53][54].…”
Section: B-cell Differentiation In Patients With CVI 207mentioning
confidence: 99%
“…Stimuli, such as allergens, may activate common immune mechanisms, which subsequently result in proteinuria in children with MCNS. Several investigators have demonstrated the potential role of Th2 cytokines in this disease [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%